The role of events in ICT adoption: same-sex marriage and Twitter. Issue 10 (3rd October 2017) - Revers, Matthias
ABSTRACT: ICT adoption is predominantly considered as a process conditioned by social structures, social situations of adopters, and attributes and features of technologies. What is often overlooked are the cultural forces that shape adoption experiences and processes. This paper focuses on events and event narratives as vehicles through which the efficacy of culture unfolds in technological change processes. Cultural sociology has shown how influential events can be for forming public opinions and facilitating collective action. This article considers the power of one event on a much smaller scale: the passage of same-sex marriage (SSM) law in New York in June 2011 was not only significant for marriage equality in the US but also for the operating logic of the news ecosystem in which the political decision was made ‒ the state house in Albany. For the journalists who covered this event on the ground, the SSM decision was the catalyst to fully embrace Twitter. Years later, the event still served as an exemplar for the potentials of Twitter and as a basis of legitimacy of associated tweeting practices reporters incorporated. This contribution is based on ethnographic research at the state house in Albany, analysis of tweets and legacy news coverage published during that period, and in-depth interviews with reporters.